PENGARUH BIG DATA ANALYTICS TERHADAP NILAI PERUSAHAAN DENGAN KUALITAS KEPUTUSAN INVESTASI SEBAGAI VARIABEL MEDIASI (Studi Empiris pada Perusahaan Sektor Perbankan yang Terdaftar di Bursa Efek Indonesia Tahun 2010-2024) - Adinda Sofia Layana Haryo Putri; Agus Purwanto (Diponegoro Journal of Accounting, 2026)
Big data analytics has become an important tool for organizations in processing large volumes of data to support strategic decision-making and improve organizational performance. This study aims to examine the effect of Big Data Analytics on firm value with investment decision quality as a mediating variable in banking sector companies listed on the Indonesia Stock Exchange during 2010–2024. This study employs panel data regression analysis using Big Data Analytics as the independent variable, firm value as the dependent variable, investment decision quality as the mediating variable, and non-performing loan as the control variable.The results show that Big Data Analytics has no effect on firm value, but it affects investment decision quality. In addition, investment decision quality has no effect on firm value and is unable to mediate the effect of Big Data Analytics on firm value.